Decarbonising end-use sectors : green hydrogen certification (International Renewable Energy Agency, 2022)
Green hydrogen - hydrogen produced from renewable energy - will play a key role in the energy transition, and particularly in the decarbonisation of hard-to-abate sectors. The deployment and uptake of green hydrogen, and the development of national, regional and international green hydrogen markets will depend on the establishment and wide acceptance of tracking systems. Such instruments are necessary to track attributes across the entire value chain, create transparency, boost demand and encourage transferability. The IRENA Coalition for Action brief on Green Hydrogen Certification, led by the members of the Decarbonising End-Use Sectors Working Group, provides an overview of technical considerations for green hydrogen tracking systems and the challenges that need to be addressed for the creation of such instruments. In addition, the brief also puts forth key recommendations to policy makers in order to successfully establish tracking systems for green hydrogen based on internationally accepted standards.